GDPNow: A model for GDP "nowcasting" - Patrick Higgins (Federal Reserve Bank of Atlanta, 2014)
This paper documents GDPNow, a "nowcasting" model for gross domestic product (GDP) growth that synthesizes the "bridge equation" approach relating GDP subcomponents to monthly source data with the factor model approach used by Giannone, Reichlin, and Small (2008). The GDPNow model forecasts GDP growth by aggregating 13 subcomponents that make up GDP with the chain-weighting methodology used by the U.S. Bureau of Economic Analysis. Using current vintage data, out-of-sample GDPNow model forecasts are found to be more accurate than a number of statistical benchmarks since 2000. Using real-time data since the second-half of 2011, GDPNow model forecasts are found to be only slightly inferior to consensus near-term GDP forecasts from Blue Chip Economic Indicators. The forecast error variance of GDP growth for each of the GDPNow model, Blue Chip, and the Federal Reserve staff's Green Book is decomposed as the sum of the forecast error covariances for the contributions to growth of the subcomponents of GDP. The decompositions show that "net exports" and "change in private inventories" are particularly difficult subcomponents to nowcast.
Keywords: E37; C53; 330; nowcasting; forecasting; macroeconometric forecasting